[PP.36.20]: CASE REPORT. (June 2015) - Dimitriu>, I.>; Raileanu, M.; Andrei, C.; Dorobantu, M.; Sinescu, C.
Abstract : Objective: Particular case of hypertension-case report Design and method: We report the case of 74 year old women, permanently hospitalized to a chronic diseases hospital, with Alzheimer disease and stroke in history, presented to our emergency unit, with one week elevated BP values around 180 / 100mmHg. At presentation the patient was obtundation, but with neurological consultation without motor deficits and brain CT with no acute injuries, only stroke sequel. Neurological and Psychiatric consultation considered neurological status in context of Alzheimer disease and stroke sequel. Patient was hospitalized in Cardiology Clinic with main diagnostic: Grade 3 Hypertension Results: A biological analysis showed severe hyponatremia. After correction of hyponatremia, neurological status of the patient improves and she shows abdominal pain diffused at both flanks. Initial investigations (abdominal x-ray, abdominal ultrasound, biochemical analysis and CBC, surgery consult) do not show significant changes. Abdominal computed tomography reveals the diagnosis: bilateral renal infarction. Note that the patient was in permanent atrial fibrillation without antithrombotic therapy and cardiac ultrasound shows voluminous thrombus in the left atrium. Conclusions: Particularity of the case is bilateral renal infarction (extremely rare incidence) with cardio embolic etiology, from a voluminous thrombus in the left atrium. The diagnosis was initially masked by neurological status due hyponatremia, side effect of diuretic therapy administered for elevated BP values, triggered by renal infarction.